A collaborative research initiative for the environmental management of ostrich production - GS Rodrigues (Revista Brasileira de Ciência Avícola, 2007)
A collaborative research initiative was proposed by the Federation of Cooperatives of Ostrich Producers of Southeastern Brazil (FECOAVESTRUZ-Sudeste) and Embrapa Environment to training technicians and to develop environmental management procedures in order to establish criteria for the definition of 'Terms of Reference' for sustainable ostrich production for FECOAVESTRUZ associates. Eight farms with different scales of operation were selected by FECOAVESTRUZ-Sudeste for the application of 'integrated environmental indicator systems', designed to develop Environmental Management Reports and to propose best management practices in the farms. The results showed that, in general, indicators relative to Use of inputs and resources, Use of veterinary inputs and raw-materials, and especially Use of energy tended to generate negative impact, because ostrich production was intensive in these farms. On the other hand, this intensive production was also associated with improvements in Income generation and Management and administration, with positive reflexes on Employment quality and Customer respect. The utilization of the 'integrated environmental indicator systems' provide fast and inexpensive procedures designed to prepare producers for the eco-certification and ensuing sustainable origin denomination for ostrich production.